2016
DOI: 10.1055/s-0036-1587158
|View full text |Cite
|
Sign up to set email alerts
|

Tumour-associated circulating microparticles: a novel liquid biopsy tool for screening and therapy monitoring of colorectal carcinoma and other epithelial neoplasia

Abstract: Up to date, novel tools for low-cost, minimal invasive cancer surveillance, cancer screening and treatment monitoring are in urgent need. Physicians consider the socalled liquid biopsy as a possible future tool successfully achieving these ultimate goals. Here, we aimed to identify circulating tumour-associated MPs (taMPs) that could aid in diagnosing minimal-invasively the presence and follow up treatment in non-small cell lung carcinoma (NSCLC), colorectal carcinoma (CRC) and pancreas carcinoma (PaCa). Tumou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Although PMPs level has been correlated with metastatic tumors, [2,4] the function of high PMPs levels in advanced melanoma still need to be explored. Our study demonstrates that circulating PMPs are …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PMPs level has been correlated with metastatic tumors, [2,4] the function of high PMPs levels in advanced melanoma still need to be explored. Our study demonstrates that circulating PMPs are …”
Section: Discussionmentioning
confidence: 99%
“…We do not have any clear explanation but we may hypothesise that PMPs reflect the tumor microenvironment, including angiogenesis, inflammatory reaction and antitumoral immunity rather than tumor burden. [5] It may also be suggested that PMPs may not be representative of tumor burden as recently suggested by Willms et al [4] Cancer-associated venous thromboembolism constitutes the second cause of death after cancer. [7] We previously observed an inverse correlation between PMPs and clotting times with a lower clotting time in stage IV patients as compared to stage III patients.…”
mentioning
confidence: 99%
“…In addition, EpCAM+CD147+ taMPs were significantly correlating with CRC tumor volume (r = 0.7288, P < 0.0001). Furthermore, EpCAM+ taMPs were found decreased after tumor resection in serum of CRC patients suggesting a close dependence with tumor presence [134] . They conclude that EpCAM+ and EpCAM+CD147+ taMPs might serve as an early indicator of cancer growth and monitor successful anti-tumour therapy and might be used as important liquid biopsy tool to differentiate between therapy responders and non-responders [134] .…”
Section: Tumor-associated Circulating Microparticlesmentioning
confidence: 92%
“…Something that we have to be in account is that exosomes do not carry cell surface markers of their origin cells however MPs carry the surface signature of their cell of origin and the quantification of MP subsets using FACS sorting allows a non-invasive assessment of cell specific pathologies. Nowadays, there are many studies which focus is to identify the most efficient surface markers of tumor associated MPs (taMPs) and liver disease [134][135][136] .…”
Section: Tumor-associated Circulating Microparticlesmentioning
confidence: 99%
“…MPs are considered to be biomarkers indicating the procoagulant state associated with a host of clinical diseases, including cancer, cardiovascular disease, sepsis and diabetes. Numerous studies have shown that the levels of circulating MPs are elevated in cancer patients, and that MPs contribute to the development of thrombosis-associated complications (9)(10)(11). MPs trigger blood coagulation and are expressed by numerous types of cancer cells (8).…”
Section: Introductionmentioning
confidence: 99%